Early Intra-Articular Complement Activation in Ankle Fractures. (21st May 2014) - Schmal, Hagen; Salzmann, Gian M.; Niemeyer, Philipp; Langenmair, Elia; Guo, Renfeng; Schneider, Conny; Habel, Maria; Riedemann, Niels
Abstract : Cytokine regulation possibly influences long term outcome following ankle fractures, but little is known about synovial fracture biochemistry. Eight patients with an ankle dislocation fracture were included in a prospective case series and matched with patients suffering from grade 2 osteochondritis dissecans (OCD) of the ankle. All fractures needed external fixation during which joint effusions were collected. Fluid analysis was done by ELISA measuring aggrecan, bFGF, IL-1 β, IGF-1, and the complement components C3a, C5a, and C5b-9. The time periods between occurrence of fracture and collection of effusion were only significantly associated with synovial aggrecan and C5b-9 levels (P < 0.001 ). Furthermore, synovial expressions of both proteins correlated with each other (P < 0.001 ). Although IL-1 β expression was relatively low, intra-articular levels correlated with C5a (P < 0.01 ) and serological C-reactive protein concentrations 2 days after surgery (P < 0.05 ). Joint effusions were initially dominated by neutrophils, but the portion of monocytes constantly increased reaching 50% at day 6 after fracture (P < 0.02 ). Whereas aggrecan and IL-1 β concentrations were not different in fracture and OCD patients, bFGF, IGF-1, and all complement components were significantly higher concentrated in ankle joints with fractures (P < 0.01 ). Complement activation and inflammatory cell infiltration characterize the joint biology following acute ankle fractures.